2001
DOI: 10.1021/jp010086y
|View full text |Cite
|
Sign up to set email alerts
|

Ion Sieving Effects in the Electrical Double Layer of Porous Carbon Electrodes:  Estimating Effective Ion Size in Electrolytic Solutions

Abstract: Certain microporous carbons have pores of molecular dimensions, the size of which can be adjusted over a wide range to fit the dimensions of a large variety of molecules. With knowing the dimensions of these molecules, size-calibrated porous carbons can be produced. In this work, we took advantage of the electronic conductivity of carbon in using it as an electrode in electrolytic solutions. By changing the electrode potential, we could induce electroadsorption and electrodesorption of ions of different dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
247
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(259 citation statements)
references
References 9 publications
12
247
0
Order By: Relevance
“…[51] The corresponding sizes of SO 2À 4 (H 2 O) 12 and H 3 O þ were reported to be 5.33 Å and 4.2 Å , respectively. [51,52] Thus, the pore size of 5.2 Å perfectly matches the size of negatively charged sulphate ions and is not too big to ''waste'' the space during accommodation of hydronium ions. Lota et al recently reported on the unchanged mobility of SO 2À 4 ions in constrained pores with a diameter of 6 Å , [53] which is in agreement with this result.…”
Section: Resultsmentioning
confidence: 79%
“…[51] The corresponding sizes of SO 2À 4 (H 2 O) 12 and H 3 O þ were reported to be 5.33 Å and 4.2 Å , respectively. [51,52] Thus, the pore size of 5.2 Å perfectly matches the size of negatively charged sulphate ions and is not too big to ''waste'' the space during accommodation of hydronium ions. Lota et al recently reported on the unchanged mobility of SO 2À 4 ions in constrained pores with a diameter of 6 Å , [53] which is in agreement with this result.…”
Section: Resultsmentioning
confidence: 79%
“…For a given porous material, the smaller the ion size, the higher the accessible surface area available to the ions. Thus, as aqueous electrolytes often have a smaller ion size than nonaqueous electrolytes, they provide, in general, higher specific capacitance values (Tables 2.2 confirm the accessibility of fine micropores, as small as 0.4-0.5 nm in diameter, to aqueous electrolytes [51,52]. As ions in electrolyte solutions are stabilized by a solvation sheath, many early studies argued that micropores were difficult to access and that mesopores, (2-50 nm) were more useful in EDLCs.…”
Section: The Electrolytementioning
confidence: 83%
“…The shape of CV resembles that for nitrogen-enriched carbons in 6 mol dm -3 KOH solution [29] and it has been explained as pseudo-capacitive interactions between cations and the nitrogen atoms of carbon, though detailed background was not given [6,29]. It was reported that alkali ions in aqueous solutions adsorb into pores of carbon materials together with sizable hydration sheath [30]. A scale of ionic effective dimensions was estimated to be 0.362 nm < K + < Na (Figs.…”
Section: Discussionmentioning
confidence: 98%